Rehabilitation With Corticobasal and Compressive Implants with Polished Surface in Case of Failure with Two Stage Implants-Article - Fodor Romulus Calin (Journal of Dentistry And Oral Implants, 2026)
The aim of this article is to present alternative possibilities for corrective intervention using corticobasal implants, following the failure of treatment with two stage implant in cases of extensive edentulism, multi-segmented edentulism, and the development of peri-implantitis 1 at the level of these implants. For this purpose, a case was selected involving a patient treated with two stage implants in a multi-segmented manner, in the distal regions of the maxilla and mandible, where the implants were affected after 12 years by peri-implantitis in proportions ranging from 20% to 100% in different areas of bone, with a predominance in the vestibular area. The decision was made to remove the affected two stage implants, as well as the remaining deciduous teeth, with or without periodontal conditions, but whose position on the arch made improperly rehabilitation, both functionally and aesthetically impossible, and made the second rehabilitation with polished corticobasal and compressive implants in immediate loading 2. Function and aesthetics of the gnathological apparatus were restored through definitive fixed metal-ceramic prosthetics on the support of corticobasal and compressive implants within 4 days from the beginning of the treatment, with the result being monitored over a period of 3 years and 3 months, and this evaluation is to continue over time. From a surgical perspective, for secondary rehabilitation with polished corticobasal and compressive implants, strategic positions in the maxillary and mandibular bones were used as follows: the fusion area of the maxillary bone with the sphenoid bone, the nasal cortex, the sinus cortex the lingual cortex distal to the mylohyoid line, and the interforaminal mandible area.34 These areas correspond to methods described in Consensus Number 6 in the IF The Foundation of Knowledge 5. In conclusion, the treatment with corticobasal, compressive polished implants is successful even in the case of a difficult clinical scenario like the one described for this patient 6. The reduced treatment time, along with the absence of the need for sinus lifts or bone grafts, makes it the ideal solution in any situation. The use of corticobasal implants, with fixation in the second/third cortical layer and an immediate loading protocol, should represent the primary solution in treating cases with poor bone representation, and no only as a “Corrective Intervention with Corticobasal® Implants”7.
Keywords: Immediate functional loading